Wave-filter-based approach for generation of a quiet space in a rectangular cavity. (1st February 2018) - Iwamoto, Hiroyuki; Tanaka, Nobuo; Sanada, Akira
Highlights: Generation of a quiet space in a rectangular cavity based on active wave control is numerically shown. Wave filtering method for a rectangular cavity using multiple microphones is newly proposed. Experiment on the proposed method is conducted, demonstrating the generation of a quiet space. Abstract: This paper is concerned with the generation of a quiet space in a rectangular cavity using active wave control methodology. It is the purpose of this paper to present the wave filtering method for a rectangular cavity using multiple microphones and its application to an adaptive feedforward control system. Firstly, the transfer matrix method is introduced for describing the wave dynamics of the sound field, and then feedforward control laws for eliminating transmitted waves is derived. Furthermore, some numerical simulations are conducted that show the best possible result of active wave control. This is followed by the derivation of the wave filtering equations that indicates the structure of the wave filter. It is clarified that the wave filter consists of three portions; modal group filter, rearrangement filter and wave decomposition filter. Next, from a numerical point of view, the accuracy of the wave decomposition filter which is expressed as a function of frequency is investigated using condition numbers. Finally, an experiment on the adaptive feedforward control system using the wave filter is carried out, demonstrating that a quiet space is generated in the target space by the proposed method.